Synthesis and characterization of superhydrophobic-superoleophilic surface - Mahadik, Satish A.; Pedraza, Fernado D.; Relekar, Brahmanand P.; Parale, Vinayak. G.; Lohar, Gaurav M.; Thorat, Sagar S. (Journal of Sol-Gel Science and Technology, 2016)
The binary superhydrophobic-superhydrophilic surface has been successfully achieved by a combination of nanoscale texture roughness on micro-textured cotton thread network by layer-by-layer deposition method through the single-step sol-gel route. Furthermore, microstructures with improved wettability were produced, in which silica nanotextures were grown without modifying the chemical method to form superoleophilic and superhydrophobic networks. A superoleophilic surface (oil contact angle 0A degrees) and a superhydrophobic coated cotton fabric with surface free energy of gamma (total) = 13. 23 +/- A 0.37 mJ m(-2) (water contact angle of 167 +/- A 1A degrees and a small sliding angle of 4 +/- A 1A degrees) were successfully obtained. The results were exemplified here by the creation of immiscible oils separation membranes, and the innumerable applications of this technology also include self-cleaning fabrics, antistaining fabrics, water purification, and antiwetting fabrics for military applications.
Keywords: contact angle; Layer-by-layer deposition method; sol-gel processing; Superhydrophobic-superoleophilic surface

Biocompatible superhydrophobic coating material for biomedical applications - Mahadik, Satish A.; Pedraza, F.; Mahadik, Sarika S.; Relekar, Brahmanand P.; Thorat, Sagar S. (Journal of Sol-Gel Science and Technology, 2017)
Biomaterials and wettability have played a crucial role in the biocompatibility with a host matrix of body fluid and cells. We discuss designing superhydrophobic biomaterials for novel applications such as temporally implant, contact lenses, controlled drug release coatings, coating on medical instruments, etc. Such Superhydrophobic coating surfaces were created with the simple dip coating method by single step base catalyst sol-gel method. Methyltriethoxysilane/trimethoxymethylsilane-based deposition at different dip periods introduces interesting properties in the region, including superhydrophobicity, biocompatibility and transparency. This works reveal the impact of interaction bone marrow mesenchymal stem cells and surface free energy on the biocompatibility of superhydrophobic biomaterial.

Lewis acid catalyzed cascade annulation of alkynols with alpha-ketoesters: a facile access to gamma-spiroketal-gamma-lactones - Kambale, Digambar A.; Thorat, Sagar S.; Pratapure, Madhukar S.; Gonnade, Rajesh G.; Kontham, Ravindar (Chemical Communications, 2017)
A novel Lewis acid catalyzed intermolecular cascade annulation of alkynols with alpha-ketoesters has been developed. This simple and efficient cascade annulation proceeds through a 5-exo-dig cyclization of alkynols followed by annulation with alpha-ketoester to provide a wide variety of unsaturated gamma-spiroketal-gamma-lactones (1,6-dioxaspiro[4.4]non-3-en-2-ones) related to many natural products.

Four-step total synthesis of (+)-yaoshanenolides A and B - Thorat, Sagar S.; Palange, Megha N.; Kontham, Ravindar (ACS Omega, 2018)
A highly concise bioinspired four-step total synthesis of yaoshanenolides A and B possessing tricyclic spirolactone with an unusual 5'H-spiro-[bicyclo[2.2.2]-oct[2] ene-7,2'-furan]-5'-one scaffold is reported. This synthesis features high-yielding aldol-type addition of gamma-butyrolactone on to the aldehyde, exocyclic olefination of lactone derivative using Eschenmoser's salt, and highly facial-and endo-selective [4 + 2]-cycloaddition of fully functionalized 5-methylene-2(5H)-furanone with natural R-(-)-alpha-phellandrene. The approach allows access to yaoshanenolides A and B in four linear steps in 11 and 13% overall yield.

Synthesis of furo[2,3-b]pyran-2-ones through Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols and alpha-ketoesters - Thorat, Sagar S.; Kataria, Priyanka; Kontham, Ravindar (Organic Letters, 2018)
Ag(I)- or Ag(I)-Au(I)-catalyzed cascade annulation of alkynols (5-hexyn-1-ol systems) with a-ketoesters involving a dual activation process (pi and sigma) has been developed for the first time. This reaction proceeds through cycloisomerization of alkynol to give the 6-endo-enol ether followed by annulation with an alpha-ketoester to furnish furo[2,3-b]pyran-2-ones in good yields. Chemical structures of all products were rigorously confirmed by single crystal X-ray analysis and analogy.

Stereoselective total synthesis of (+/-)-pleurospiroketals A and B - Thorat, Sagar S.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2021)
A full account of our efforts toward the stereoselective total synthesis of sesquiterpenoid-derived natural products (+/-)-pleurospiroketals A and B is described. Commercially available 3-methyl-2-cyclohexenone and 2,2-dimethyloxirane were used as key building blocks, and the substrate-controlled stereoselection was exploited to access the entire stereochemistry of these natural products. Initially, a planned synthetic route involving a [6,5]-bicyclic lactone intermediate was found to be insurmountable, and the later strategy comprising OsO4-NMO-mediated dihydroxylation of 3-methyl-2-cyclohexenone, followed by Luche reduction, Eschenmoser methylenation, and Bronsted acid-induced spiroketalization steps, was ultimately identified as the reliable strategy.

Strategies for the synthesis of furo-pyranones and their application in the total synthesis of related natural products - Thorat, Sagar S.; Kontham, Ravindar (Organic Chemistry Frontiers, 2021)
The furo-pyranone framework is widely present in the molecular structure of various biologically potent natural products and un-natural small molecules, and it represents a valuable target in synthetic organic chemistry and medicinal chemistry. In the last five decades, numerous innovative synthetic methodologies have been disclosed for these bis-oxacyclic fused heterocycles, expanding the scope of accessible building blocks, efficient and affordable catalysis, facile reaction conditions, and overall practicality of the process. In this comprehensive review article, we focus on showcasing the complete spectrum (from the first report in the 1970s to the latest disclosure in 2020) of efforts devoted towards the synthesis of diverse classes of furo-pyranones through systematization and critical analysis of the accumulated experimental knowledge and their elegant applications in total syntheses of biologically interesting related natural products.

Ready access to benzannulated [5,5]-oxaspirolactones using Au(III)-catalyzed cascade cyclizations - Mankad, Yash; Thorat, Sagar S.; Das, Pronay; Krishna, Gamidi Rama; Kontham, Ravindar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
This work showcases an unprecedented Au(III)-catalyzed cascade cyclization of 2-(4-hydroxyalkynyl)benzoates to access benzannulated [5,5]-oxaspirolactones related to biologically active natural products. This reaction proceeds through an initial 5-endo-dig mode of hydroalkoxylation of the alkynol segment to give the oxocarbenium species (via cyclic enol-ether) followed by the addition of carboxylate onto the oxocarbenium that delivers the oxaspirolactone scaffold. While testing this method's scope, we found that the steric and electronic environment of the hydroxyl group could alter the reaction pathway that delivers isochromenone through a competitive 6-endo-dig mode of attack of the carboxylate onto the tethered alkyne.

Silver-catalyzed [3 + 3]-annulation cascade of alkynyl alcohols and α,β-unsaturated ketones for the regioselective assembly of chromanes - Nakate, Ashwini K.; Thorat, Sagar S.; Jain, Shailja; Rama Krishna, Gamidi; Vanka, Kumar; Kontham, Ravindar (Organic Chemistry Frontiers, 2022)
An unprecedented Ag(i)-catalyzed [3 + 3]-annulation of alkynyl alcohols (5-hexyn-1-ols) and α,β-unsaturated ketones is reported to construct simple to complex chromanes. This transformation begins with hydroalkoxylation of alkynol through C–C triple bond activation to give cyclic-enol ether, followed by intermolecular 1,4-addition and intramolecular 1,2-addition of enol ethers onto the enone and oxidative aromatization or Grob-type elimination steps. Facile reaction conditions, broad substrate scope, good to excellent yields, and atom economy are the salient features of this protocol. Isolation of the active pyran-tethered cyclohexadiene reaction intermediate, additional supporting experiments, and DFT calculations strongly support the experimental findings and corroborate our proposed mechanism.

Regioselective synthesis of benzannulated [5,6]-oxaspirolactones via Cu(II)-catalyzed cycloisomerization of 2-(5-Hydroxyalkynyl)benzoates - Thorat, Sagar S.; Shimpi, Sagar P.; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Spiroketals and oxaspirolactones are widely found in biologically active natural products, serving as important structural motifs. In this study, we present a Cu-(II)-catalyzed cascade cycloisomerization of 2-(5-hydroxyalkynyl)-benzoates, enabling the regioselective synthesis of benzannulated [5,6]-oxaspirolactones containing an isochromen-1-one moiety. This strategy offers a rapid and efficient approach to access a diverse array of benzannulated [5,6]-oxaspirolactones. The methodology presented here showcases a broad substrate scope, delivering good yields and scalability up to gram scale. The structures of the oxaspirolactones were unequivocally confirmed through single-crystal X-ray analysis and by analogy using H-1 and C-13-H-1 NMR data.
Keywords: Construction; Isocumarins; Strategies

Studies on the stereoselective synthesis of sacubitril via a chiral amine transfer approach - Sadanande, Megha V.; Thorat, Sagar S.; Sharma, Himanshu; Singh, Geetika; Vanka, Kumar; Gonnade, Rajesh G.; Kontham, Ravindar (Chemistry-An Asian Journal, 2025)
We present a comprehensive account of our efforts directed towards the synthesis of sacubitril, a neprilysin inhibitor used in combination with valsartan and marketed as Entresto (TM). Our initial approach to the formal synthesis of sacubitril employed a chiral pool strategy, utilizing (S)-pyroglutamic acid as a key building block and Cu(I)-mediated Csp2-Csp3 cross-coupling as a key transformation. Further investigations led to the development of chiral amine transfer (CAT) reagents-based stereoselective synthesis. This involved the E-selective construction of gamma-ylidene-butenolide from readily available biphenyl bromide and 4-pentynoic acid, the conversion of this butenolide to its ene-lactam using chiral amine, and substrate-controlled diastereoselective reduction of ene-lactam using Et3SiH or Pd/C, H2 (overall chiral amine transfer) as key transformations. Antipodal lactam intermediates were synthesized using corresponding chiral amines, and the stereochemical outcomes during the ene-lactam reduction with Et3SiH were rationalized by DFT studies.
Keywords: Chiral Amine Transfer (CAT) approach; Chiral pool approach; Sacubitril; stereoselective synthesis